2014
DOI: 10.1007/s00134-014-3576-1
|View full text |Cite
|
Sign up to set email alerts
|

Volume expansion in the first 4 days of shock: a prospective multicentre study in 19 French intensive care units

Abstract: High between-centre variability characterised all the aspects of FB prescription and monitoring, but overall haemodynamic exploration to help guide and monitor FB was infrequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
4
47
0
2
Order By: Relevance
“…Fluid boluses Increasing focus on the uncertain efficacy of fluid boluses on oliguria in ICU patients The results of the before-and-after studies questioning the effects of fluid boluses on urinary output in clinical practice [75] are now supported by RCT data [76] Fluid volumes Increasing focus on the negative effects of higher fluid volumes in critically ill patients, in particular those with established AKI…”
Section: Hes Solutionsmentioning
confidence: 99%
“…Fluid boluses Increasing focus on the uncertain efficacy of fluid boluses on oliguria in ICU patients The results of the before-and-after studies questioning the effects of fluid boluses on urinary output in clinical practice [75] are now supported by RCT data [76] Fluid volumes Increasing focus on the negative effects of higher fluid volumes in critically ill patients, in particular those with established AKI…”
Section: Hes Solutionsmentioning
confidence: 99%
“…Previous point prevalence studies have shown that clinical practice is, with some variation, quite simple [2][3][4]. The indications for intravenous fluid administration relate mainly to low blood pressure, high plasma lactate and low urinary output.…”
Section: Introductionmentioning
confidence: 99%
“…echocardiography, to guide their fluid therapy. The fluids used are mainly crystalloid solutions, both saline and buffered solutions, and if a colloid is used, it is albumin [2,3,5]. While this practice may be well within the current evidence base, the observations raise some questions.…”
Section: Introductionmentioning
confidence: 99%
“…1). The way fluid management is delivered is not standardized, as reflected by the high variability in the way fluid boluses are decided and guided in real life practice [5]. There is a lack of randomised controlled trials testing different strategies of volume expansion based on objectives measurements during the first days of septic shock.…”
mentioning
confidence: 99%
“…There is a lack of randomised controlled trials testing different strategies of volume expansion based on objectives measurements during the first days of septic shock. Neither the systematic use of the well-known (but rarely used in ICU practice [5]) fluid challenge technique [6][7][8] nor the systematic use of the few available predictive indices of fluid responsiveness [9,10], have been tested against usual care with hard endpoints such as mortality. Conducting such trials is very challenging for physiological reasons (haemodynamic instability does not have a single cause and ''one size fits all'' algorithm are intrinsically deemed to fail) and for logistical reasons (24/24, 7/7 availability of investigators; rigorous protocol and risk of protocol violation/deviation; need of large sample sizes).…”
mentioning
confidence: 99%